Assessment of habitat change and threats to the greater one-horned rhino (Rhinoceros unicornis) in Pabitora Wildlife Sanctuary, Assam, using multi-temporal satellite data - Sarma, Pranjit; Talukdar, Bibhab; Sarma, Kiranmay; Barua, Mrigen (Pachyderm, 2009)
Pabitora Wildlife Sanctuary (WLS), located in north-eastern India, is a prime habitat for Rhinoceros unicornis, Indian or greater one-horned rhinos. With a population of 84 rhinos, Pabitora WLS has the proud legacy of sheltering the highest density of Indian rhinos in the world. Although the total notified area of the sanctuary is 38.80 km 2 , the state government of Assam is yet to handover an area of 11.07 km 2 to the sanctuary authority. As such, the Department of Environment and Forests, Assam presently manages a total area of only 27.73 km 2 . Only 12.57 km 2 has been found to be suitable as rhino habitat. Satellite imagery from 1977, 1999 and 2004 was analysed for assessment of rhino habitat change in Pabitora WLS. Results indicate that there is a substantial increase in woodland (34.51%) accompanied by decline in alluvial grassland (68%) from 1977 to 2004 within the sanctuary area of 38.80 km 2 . This change of habitat is mostly because of the natural succession process, local livestock grazing and improper management of the grassland habitat. In this paper, we recommended a set of habitat management protocols for the restoration of key habitats in Pabitora WLS. Key words: Indian rhino, Pabitora, habitat change, remote sensing, threats Le Sanctuaire de la Faune (SF) de Pabitora, situé au nord-est de l’Inde, est un habitat principal du Rhinocéros unicornis, le grand rhinocéros unicorne ou indien. Ayant une population de 81 rhinocéros en 2006, le SF Pabitora a le fier héritage d’abriter la densité la plus élevée de rhinocéros indiens dans le monde. Bien que la superficie totale notifiée du sanctuaire soit 38,80 km 2 , le gouvernement de l’état d’Assam doit encore remettre une superficie de 11,07 km 2 à l’autorité du sanctuaire. Par conséquent, le Département de l’Environnement et des Forêts de l’Assam ne gère actuellement qu’une superficie totale de 27,73 km 2 . On trouve que 12,57 km 2 seulement conviennent comme habitat au rhinocéros. Les images satellitaires de 1977, 1999 et 2004 ont été analysées pour évaluer le changement de l’habitat du rhinocéros dans le SF Pabitora. Les résultats indiquent qu’il y a une augmentation substantielle de la zone boisée (34,51%) accompagnée d’un déclin des herbages alluviaux (68%) entre 1977 et 2004 au sein du sanctuaire de 38,80 km 2 . Ce changement d’habitat est principalement dû au processus naturel de succession, au bétail local qui paît et à une mauvaise gestion de l’habitat des herbages. Dans ce document, nous avons recommandé un ensemble de protocoles de gestion de l’habitat afin de restaurer des habitats clés dans le Sanctuaire de la Faune de Pabitora.